MARKETING GASTRONÓMICO Y SU IMPACTO EN LA RENTABILIDAD ECONÓMICA DE LOS EMPRENDIMIENTOS DEL CANTÓN QUEVEDO, AÑO 2022 - Corozo Moreira, Darian LIsseth (2022)
The city of Quevedo is one of the most commercial cities in the country, encompassing a large number of spaces for restaurants, supermarkets, etc. The city increasingly evidences a continuous development as a result of the culture, personality and taste of the citizens. The enterprises of the City of Quevedo capture a marketing plan to publicize the attributes of Quevedo gastronomy in this way, making the customer fall in love, in order to provide them with good-tasting and quality products. The success of companies and products depends on the progress and creativity of companies, so it is necessary to establish actions that formalize and specify the form or methods of communication, care and delivery of products that satisfy the food desires of customers and give know all the characteristics and competitive advantages of these products A descriptive investigation was used where the high degree of incidence and implementation of the present project was determined, which will contribute to the profitability of the enterprises, generating development opportunities for the population.